Struktur Ritual dan Makna Semantis pada Tradisi Pernikahan Masyarakat Suku Samin Bojonegoro, Jawa Timur: Studi Etnolinguistik - Kharirin, Nur; Hamida, Layli (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2025)
This study examines the ritual structure including ethnographic components of communication and semantic meaning contained in the communication of the marriage tradition of the Samin community in Bojonegoro, East Jawa through an ethnographic approach to communication. The research method used is ethnography with a qualitative approach. Data were collected through participant observation, field notes, and semi-structured interviews. The findings of this study indicate that the Bojonegoro Samin wedding tradition has a unique ritual structure and has a symbolic meaning in it. Each stage of the ritual, from the answering procession to the giving of advice by the elders, then Dell Hymes' SPEAKING communication ethnography component as the reference theory, reflects the cultural values of the Samin people who uphold simplicity, honesty, and togetherness. In addition, this study also found that the language used in the marriage tradition of the Samin community has many lexicons that have deep semantic meaning. These lexicons not only function as a means of communication, but also as a representation of the cultural values and local wisdom of the Samin people of Bojonegoro, East Java.